Long-lasting chemiluminescence bioassays for glucose enabled by a MOFs-in-hydrogel hybrid platform. Issue 5 (5th August 2022) - Song, Minghao; Shi, Feifei; Zhang, Ran; Wang, Xueying; Sun, Xiaojun; Li, Yuyang; Ren, Xiang; Ma, Hongmin; Wei, Qin
Abstract : Chemiluminescence (CL) bioassays with stable long-lasting signal outputs have rekindled interest due to their promising application potential in various fields. Abstract : Chemiluminescence (CL) bioassays with stable long-lasting signal outputs have rekindled interest due to their promising application potential in various fields. In this study, long-lasting chemiluminescence bioassays for glucose were achieved by incorporating metal–organic frameworks (MOFs) in an agarose hydrogel matrix. Zeolitic imidazolate framework-8 (ZIF-8) was used as a matrix to load glucose oxidase (GOx) and zeolitic imidazolate framework-67 (ZIF-67) was used as a nanomimic of peroxidase to promote the CL reactions of luminol. ZIF-8 protects the GOx from denaturation under high temperatures for gel formation and enables its slow release due to its pH-responsive capability. Agarose hydrogel was used as a scaffold to disperse the MOF nanocrystals and inhibit molecular diffusion. Based on the achieved strong and long-lasting chemiluminescence signals, cascade catalytic bioassays with a wide detection range were proposed for the sensitive detection of glucose. The detection range of glucose by CL analysis was 0.2–100 mmol L −1 under optimal conditions, and the detection limit was 0.011 mmol L −1 (S/N = 3).